Loss of endophilin-B1 exacerbates Alzheimer's disease pathology. (16th May 2015) - Wang, David B.; Kinoshita, Yoshito; Kinoshita, Chizuru; Uo, Takuma; Sopher, Bryce L.; Cudaback, Eiron; Keene, C. Dirk; Bilousova, Tina; Gylys, Karen; Case, Amanda; Jayadev, Suman; Wang, Hong-Gang; et al.
Abstract : Neuron-specific isoforms of Endophilin-B1, also known as Bax-interacting factor-1 (Bif-1), are neuroprotective. Wang et al. reveal reduced expression of these variants in Alzheimer's disease, and propose the existence of a feed-forward mechanism whereby beta-amyloid suppresses neuron-specific Bif-1, which in turn enhances beta-amyloid accumulation and neuronal vulnerability to stress. Abstract : Abstract : Endophilin-B1, also known as Bax-interacting factor 1 (Bif-1, and encoded by SH3GLB1 ), is a multifunctional protein involved in apoptosis, autophagy and mitochondrial function. We recently described a unique neuroprotective role for neuron-specific alternatively spliced isoforms of endophilin-B1. To examine whether endophilin-B1-mediated neuroprotection could be a novel therapeutic target for Alzheimer's disease we used a double mutant amyloid precursor protein and presenilin 1 (APPswe/PSEN1dE9) mouse model of Alzheimer's disease and observed that expression of neuron-specific endophilin-B1 isoforms declined with disease progression. To determine if this reduction in endophilin-B1 has a functional role in Alzheimer's disease pathogenesis, we crossed endophilin-B1 −/− mice with APPswe/PSEN1dE9 mice. Deletion of endophilin-B1 accelerated disease onset and progression in 6-month-old APPswe/PSEN1dE9/endophilin-B1 −/− mice, which showed more plaques, astrogliosis, synaptic degeneration, cognitive impairment and mortality than APPswe/PSEN1dE9 mice. In mouse primary cortical neuron cultures, overexpression of neuron-specific endophilin-B1 isoforms protected against amyloid-β-induced apoptosis and mitochondrial dysfunction. Additionally, protein and mRNA levels of neuron-specific endophilin-B1 isoforms were also selectively decreased in the cerebral cortex and in the synaptic compartment of patients with Alzheimer's disease. Flow sorting of synaptosomes from patients with Alzheimer's disease demonstrated a negative correlation between amyloid-β and endophilin-B1 levels. The importance of endophilin-B1 in neuronal function was further underscored by the development of synaptic degeneration and cognitive and motor impairment in endophilin-B1 −/− mice by 12 months. Our findings suggest that endophilin-B1 is a key mediator of a feed-forward mechanism of Alzheimer's disease pathogenesis where amyloid-β reduces neuron-specific endophilin-B1, which in turn enhances amyloid-β accumulation and neuronal vulnerability to stress.